Manajemen Kepala Sekolah dalam Meningkatkan Kinerja Guru di SMA Negeri 2 Tarutung - Dahlan Situmeang; Binur Panjaitan; Hasudungan Simatupang (STIKes Ibnu Sina Ajibarang, 2023)
The objectives of this research are: 1) to determine the Principal's management planning in improving teacher performance at SMA Negeri 2 Tarutung; 2) to determine the organization of the Principal's management in improving teacher performance at SMA Negeri 2 Tarutung; 3) to determine the implementation of the Principal's management in improving teacher performance at SMA Negeri 2 Tarutung; 4) to determine the Principal's management supervision in improving teacher performance at SMA Negeri 2 Tarutung. The research method used in this research is a qualitative method using a natural qualitative approach. The subjects in this research were taken directly from parties who are directly related to the implementation of Principal Management in improving the function and performance of teachers. In seeking this information the researcher will interview: (1) Principal, (2) Deputy Principal, (3) Teacher and can develop according to the needs of researchers. The results obtained in this research are: 1) The planning process for improving teacher performance at SMA Negeri 2 Tarutung began with holding meetings covering all school activities, including curriculum, student affairs, infrastructure and public relations; 2) Organizing activities at SMA Negeri 2 Tarutung are carried out by considering the 5W and 1H principles, with the aim that the activities to be carried out can be right on target and efficient; 3) To improve teacher performance at SMA Negeri 2 Tarutung, various steps were taken, including involving teachers in workshops, IT in-depth training, developing report-based assessments, developing an Internal Quality Assurance System (SPMI), training in developing learning implementation plans (RPP), technical guidance (bimtek) for learning, preparation of literacy questions, preparation of DUPAK, as well as personal coaching for teaching staff; 4) Improving teacher performance at SMA Negeri 2 Tarutung is carried out through two supervision systems, namely internal supervisors and external supervisors.